2019
DOI: 10.1037/aap0000154
|View full text |Cite
|
Sign up to set email alerts
|

Caught between “light skin is beautiful and tanned skin is attractive”: How bicultural socialization shapes attitudes toward skin color aesthetics.

Abstract: Cultural socialization is a convoluted process involving sociocultural contexts and human interactions. Migration, immigration, and intercountry adoption has complicated such contexts. Based on two groups of female Chinese descendants who grew up in the United States and live in between two cultures, this study explores how bicultural socialization shapes individuals’ aesthetic attitudes toward skin color through interviews with 15 second-generation Chinese Americans raised in the United States by first-genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…This skin tone guide permitted the participant and researcher to choose a shade with a unique undertone and level of lightness to best fit each participant's skin tone. We are only aware of one peer-reviewed study that used this measure for perceived self-evaluation in Chinese Americans, see Chen et al (2019). Most prior studies assessed the perception of skin tone by utilizing general ratings such as "very dark or very light skinned" (e.g., Thompson & Keith, 2001), with one notable exception, when researchers measured the amount of light that reflects off the skin by utilizing spectrometers or reflectometers (e.g., Dent et al, 2020).…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This skin tone guide permitted the participant and researcher to choose a shade with a unique undertone and level of lightness to best fit each participant's skin tone. We are only aware of one peer-reviewed study that used this measure for perceived self-evaluation in Chinese Americans, see Chen et al (2019). Most prior studies assessed the perception of skin tone by utilizing general ratings such as "very dark or very light skinned" (e.g., Thompson & Keith, 2001), with one notable exception, when researchers measured the amount of light that reflects off the skin by utilizing spectrometers or reflectometers (e.g., Dent et al, 2020).…”
Section: The Current Studymentioning
confidence: 99%
“…No peer-reviewed studies, to our knowledge, have assessed both actual and perceived skin tones in Black American women using an objective measure such as the Pantone Skin Tone guide (Pantone, 2017, but see Chen et al, 2019 that employed this measure for perceived self-evaluations in Chinese Americans). This research was conducted by utilizing a skin tone guide that has one hundred and ten shades and is designed to cover a wide range of skin tones.…”
mentioning
confidence: 99%
“…Chinese people internationally are often [ 8 , 10 , 28 , 38 ]—but not always [ 16 , 27 , 39 ]—grouped into Asian and East Asian categories for studies related to skin cancer rates and behavioral risks, impeding extrapolation for subgroups. Only 2 studies were identified comparing the perspectives on the risks of skin cancer among specific ethnic Chinese populations from different sociocultural backgrounds [ 38 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The messages reflected in this learning process may influence bicultural identity development by encouraging the dual adoption of traditionally American (e.g., individualism and competition) and heritage-specific ideals. What may emerge from family cultural socialization is the acquisition of bicultural competencies—skills for juggling the different sets of affective, behavioral, and cognitive expectations tied to their group memberships—that may enable immigrant and refugee youth to navigate the different contextual pressures that stem from belonging to multiple cultures (Chen et al, 2019; Huynh et al, 2018; Nguyen & Benet-Martínez, 2013).…”
mentioning
confidence: 99%
“…Umaña-Taylor and Hill’s (2020) subsequent review of the family ethnic–racial socialization literature in the last two decades additionally highlighted positive associations between cultural socialization and other adjustment indicators such as self-esteem, academic adjustment, adaptive coping, and psychological well-being. However, few studies have attended the role of family in emerging adults’ bicultural identity development (Chen et al, 2019; Ferrari et al, 2019). No studies to date have focused on clarifying the relations between family cultural socialization and bicultural harmony and blendedness, which may shed more light on the bicultural identity negotiation process and its outcomes for Burmese refugees (Huynh et al, 2018).…”
mentioning
confidence: 99%